Black colleges across the diaspora : global perspectives on race and stratification in postsecondary education - Brown, M. Christopher; Dancy, T. Elon (Bingley, U.K. : Emerald Publishing Limited, 2017)
This book examines colleges and universities across the diaspora with majority African, African-American, and other Black designated student enrollments. The nomenclature of this cohort connotes an assumption of racial exclusivity and homogenous monolithism. Research confirms that these campuses possess a flourishing landscape with racial, economic, and gender diversity while sharing a Black identity created through global racialization. Globally, Black colleges and universities create academic and social environments where different races, sexes, cultures, languages, nationalities, and citizenship status coexist, enabling academic achievement, civic engagement, and colonial resistance. This volume highlights racial hegemony in multi-national student experiences and achievement; examines the social and career implications of attendance on lifelong success; explores the impact of global Black marginalization and racist ideology on Black college communities; and explores the role gender plays in outcomes and attainment. This book engages the diversity of black colleges and universities and explains their critical role in promoting academic excellence in higher education.
Includes index.
Includes bibliographical references.
Keywords: Universities and colleges, Black; Race relations -- Study and teaching (Higher); Education, Higher -- Social aspects